Results of the CARNet programme "Educational Projects" - Prišćan, Sonja (Array, 2003)
Summary The Croatian Academic and Research Network - CARNet launched the programme "Educational Projects" in 2000 in order to explore how the use of information technology fits within the educational system of Croatian institutions of higher education, to define recommendations for all entities included in the high education system, and to launch technical support centres for the application of ICT in teaching. The research was carried out by launching and monitoring nine educational projects at Croatian institutions of higher education, which was done through the stage of the preparation of materials in the digital form and the stage of their use in teaching. The methods used in the program are surveys, interviews and monitoring of the on-line courses.